The Sodium Rhodizonate Test a Specific Test for Heavy Metals in Gunshot Residues - Üner, Hüseyin Bülent; Çerkezoğlu, Ali; Şam, Bülent (The Bulletin of Legal Medicine, 1997)
The Gunshot ıesidues and the methods for the determination of shooting distance were introduced. The factors may influence the distribution of gunshot residues on a target were explained. The Sodium Rhodizonate Test was used to detect gunshot residues (lead, barium, antimony) and their distribution patterns on garments. The application of this method is much more sensitive and easy compared to the other methods reported.Key Words: Sodium Rhodizonate, Gunshot Residues, Distance Determination.
Keywords: sodium rhodizonate; gunshot residues; distance determination